Probable airborne transmission of SARS-CoV-2 in a poorly ventilated restaurant - Li, Yuguo; Qian, Hua; Hang, Jian; Chen, Xuguang; Cheng, Pan; Ling, Hong; Wang, Shengqi; Liang, Peng; Li, Jiansen; Xiao, Shenglan; Wei, Jianjian; Liu, Li; et al. (Building and environment, 2021)
Although airborne transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been recognized, the condition of ventilation for its occurrence is still being debated. We analyzed a coronavirus disease 2019 (COVID-19) outbreak involving three families in a restaurant in Guangzhou, China, assessed the possibility of airborne transmission, and characterized the associated environmental conditions. We collected epidemiological data, obtained a full video recording and seating records from the restaurant, and measured the dispersion of a warm tracer gas as a surrogate for exhaled droplets from the index case. Computer simulations were performed to simulate the spread of fine exhaled droplets. We compared the in-room location of subsequently infected cases and spread of the simulated virus-laden aerosol tracer. The ventilation rate was measured using the tracer gas concentration decay method. This outbreak involved ten infected persons in three families (A, B, C). All ten persons ate lunch at three neighboring tables at the same restaurant on January 24, 2020. None of the restaurant staff or the 68 patrons at the other 15 tables became infected. During this occasion, the measured ventilation rate was 0.9 L/s per person. No close contact or fomite contact was identified, aside from back-to-back sitting in some cases. Analysis of the airflow dynamics indicates that the infection distribution is consistent with a spread pattern representative of long-range transmission of exhaled virus-laden aerosols. Airborne transmission of the SARS-CoV-2 virus is possible in crowded space with a ventilation rate of 1 L/s per person. [Display omitted] •This outbreak involved ten infected persons in three families.•Full video recording at time of infection allows restoration of the scene.•Time-averaged ventilation rates were only 0.9 L/s per person in the restaurant.•Insufficient ventilation played a role in this outbreak of COVID-19.